Design a Condition Monitoring System for Rotating Machinery Gearboxes by Oil Quality Measurements and Vibration Analyses - Gohari, Mohammad; Tahmasebi, Mona; Ghorbani, Mahdi (Control Systems and Optimization Letters, 2023)
Every year high costs are expending to repair rotating machinery in factories and industrial centers due to failures. Most failures happen suddenly while by condition monitoring of systems prognosis and diagnosis are possible. By condition monitoring, the failures can be detected and solved in the early stages. Gearboxes are an element used widely, and applying condition monitoring for them makes a significant benefit for saving budget due to prognosis and removing failure before progress. The current paper aims to present a condition monitoring system for gearbox which is able to inspect lubricant by oil temperature and pH. Moreover, it can detect some defects in the gearbox by vibration analyses such as unbalance, bent shaft, looseness in bearing housing, and whirl of oil. The evaluation of the system shows that its accuracy is proper for use in gearboxes.